The Astronic Tradition: Understanding the Role of Celestial Observation in Religion - Belay Sitotaw Goshu (Britain International for Academic Research (BIAR) Publisher, 2024)
The Astronic Tradition explores the profound influence of celestial observation on religious beliefs and practices across cultures. This study investigates how ancient civilizations utilized astronomical phenomena to shape their spiritual frameworks and the ongoing relevance of these traditions in contemporary religious contexts. Historical evidence reveals that societies such as the Mesopotamians and Egyptians closely monitored celestial events, integrating them into their calendars and rituals. This study highlights the common human experience of looking to the cosmos for significance by contrasting how major religions Hinduism, Christianity, and Islam interpret celestial phenomena. It also fills the gaps in the literature on non-Western viewpoints and the contemporary significance of celestial gazing in religious rituals. The results promote discussion on how modern religious communities might incorporate astronomical knowledge into their beliefs and advance our understanding of the relationship between science and spirituality. Finally, this study promotes more interdisciplinary research and highlights the timeless importance of cosmic gazing in forming human spirituality.